An extension of quaternionic metrics to octonions - Marques, S. (1985)
A treatment of a non-Riemannian geometry including internal complex, quaternionic, and octonionic space is made. Then, an interpretation of this geometry for the nonsymmetric theory of Einstein-Schrödinger, and for the unified theory of Borchsenius is showed. Finally, field equations in the extended octonionic geometry of space-time are obtained through a minimal action principle.